MACRONUTRIENTS OF MOTHERS’ MILK OF VERY LOW BIRTH WEIGHT INFANTS: ANALYSIS ACCORDING TO GESTATIONAL AGE AND MATERNAL VARIABLES - Moreira, Maria Elisabeth Lopes (Rev Paul Pediatr, 2020)
OBJECTIVE: To analyze the composition of macronutrients present in the milk of mothers of preterm newborn infants (PTNB) - protein, fat, carbohydrate, and calories - by gestational age (GA), chronological age (CA) and maternal variables. METHODS: Longitudinal study that analyzed 215 milk samples from the 51 mothers of PTNB admitted in three Neonatal Intensive Care Units of Rio de Janeiro from May/2013-January/2014. Milk collection was performed by pickup pump, on a fixed day of each week until discharge. The spectrophotometric technique with Infrared Analysis (MilkoScan Minor 104) was used for the quantitative analysis. A sample of 7 mL of human milk was taken from the total volume of milk extracted by the mother. The data was grouped by GA (25-27, 28-31, 32-36, 37-40 weeks) and by CA (zero to 4, 5-8, 9-12, 13-16 weeks). RESULTS: Protein, carbohydrate, fat and calories did not show any pattern of change, with no difference among groups of GA. When the macronutrients were analyzed by groups of CA, protein decreased, with significant difference between the first two groups of CA. Carbohydrates, fat and calories presented increasing values in all groups, without significant differences. Weight gain during pregnancy, maternal hypertension and maternal age were associated with changes in fat and calories in the first moment of the analysis of milk. CONCLUSIONS: There was a significant decrease in the levels of protein during the first eight weeks after birth. CA may be an important factor in the composition of human milk.